Effect of Mentoring Program on Mentee Outcomes at Malaysian Institutions of Higher Learning in Sarawak - Azman, Ismail; Kho, Michael Khian Jui; Rizal, Abu Bakar; Fatahyah, Yahya; Yusof, Ismail; Nurita, Juhdi (2013)
Purpose:Thisstudy was conducted primarily to measure the relationship between mentoring program and mentee outcomes.Design/methodology/approach:A survey methodwas employed to gather250 usable self-report questionnaires from undergraduate students atMalaysian institutions of higher learning in Sarawak, Malaysia.Findings and Originality/Value:Themain outcomeof SmartPLS path model confirmed that mentoring program does act as an important determinant of mentees’ psychosocial and academic performance in the studied organizations.Practical implications:Organizations can benefit from theresults and recommendationsof this research. In improving their mentoring programs,organizations should practise communication openness and provide adequate support both to mentors and mentees. These initiatives may lead to sustainable and increased performance of institutions of higher learning.Originality/value:This study revealsthat management is responsibleto appropriately implement communication and support in mentoring relationships can enhance mentees’ psychosocial and academic performancein Malaysian institutions of higher learning.